GE_GERICHTE P/20397/2017 vom 14. Januar 2019 - GE Cour de justice (2019)
FIXATION DE LA PEINE ; CONCOURS D'INFRACTIONS ; ACTE D'ACCUSATION ; PRINCIPE DE L'ACCUSATION | CP.139.al1; CP.139.al2; CP.139.al3; CP.47; CP.49; CPP.325